2021
DOI: 10.1177/08862605211021974
|View full text |Cite
|
Sign up to set email alerts
|

Police are Influenced by Anchoring and Risk When Allocating Resources for Scenario-based Intimate Partner Violence Cases

Abstract: Sixty-six police officers were given four intimate partner violence (IPV) scenarios to rate for risk of future violence. At the start of the experiment, participants were provided with either a low-risk or high-risk “anchor” scenario of police attending an IPV incident. Next, participants were given three counterbalanced scenarios: high, medium, and low risk. Half the participants were given a structured professional judgment tool to guide their decisions. Participants given the low-risk anchor rated the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Third, supporting Hypothesis 1c, our results showed that perceived severity of IPVAW was related to proactive attitudes towards intervention in IPVAW cases, which is in accord with prior research (Goodson et al, 2022;Gracia et al, 2008;Kebbell, 2022). Importantly, the tested mediation model confirmed that the perceived severity of IPVAW is the explanatory mechanism that underlies the negative relationship between IPVAW myths and proactive attitudes toward intervention in gender violence, confirming our Hypothesis 2.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Third, supporting Hypothesis 1c, our results showed that perceived severity of IPVAW was related to proactive attitudes towards intervention in IPVAW cases, which is in accord with prior research (Goodson et al, 2022;Gracia et al, 2008;Kebbell, 2022). Importantly, the tested mediation model confirmed that the perceived severity of IPVAW is the explanatory mechanism that underlies the negative relationship between IPVAW myths and proactive attitudes toward intervention in gender violence, confirming our Hypothesis 2.…”
Section: Discussionsupporting
confidence: 90%
“…Drawing from Banyard's bystander intervention model ( 2011), studies also have indicated that the perceived severity of IPVAW is an influencing factor in the decision-making process involved in providing help in gender-based violence episodes (Banyard, 2011;Gracia et al, 2008Gracia et al, , 2009. A cross-cultural body of research has indicated that perception of severity, urgency, or high risk in IPVAW cases promoted the allocation of additional resources in Australia (Kebbell, 2022), lesser legitimization, and higher credibility and service referral in the U.S. (Goodson et al, 2022), as well as preferences for actions regardless of the victim's wishes and stronger feelings of responsibility in Spain (Gracia et al, 2008). However, even though police officers tend to recognize and prefer greater involvement, nuances have been found concerning how they evaluate the severity of different IPVAW incidents (Gracia et al, 2008;Robinson et al, 2016).…”
Section: Ipvaw Myths and Police Officers' Perceived Severity Of Ipvawmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, repeated exposure to low-level violence may increase frontline officers' complacency and sense of futility in their role (Stark, 2012). An alternative interpretation may be that officers with more negative attitudes perceive DFV incidents as less severe which would align with the anchoring effects seen in Kebbell (2022).…”
Section: Frequency and Severity Of Dfv Incidentsmentioning
confidence: 90%
“…Higher perceived severity of DFV is associated with lower endorsement of myths (i.e., beliefs that minimize or justify DFV) and a greater willingness to intervene (Serrano-Montilla et al, 2023). Conversely, the presence of anchoring effects and working in an environment characterized by more frequent and higher levels of violence can potentially influence perceptions and desensitize officers to the risks involved (Kebbell, 2022). Is therefore reasonable to expect a dose effect whereby the frequency of attendance at DFV and the level of violence encountered have an influence on officer stress, attitudes, and performance-although the directionality is uncertain.…”
Section: Frequency and Severity Of Incidentsmentioning
confidence: 99%